The Heretic Nature of Al-Qaeda’s Ideology - Ararat Kostanian (Jurnal Studi Sosial dan Politik, 2021)
The purpose of the article is to illustrate the ideological aspect of Al-Qaeda that constitutes the pillar of the organisation based on distinct interpretation of Quran and biased understanding of the meaning of Jihad. The functional method of Al-Qaeda is not simplistic or unsystematic, aimed at a particular target or focused or specific country or region. In my findings, it is evident that the formation of such transnational organisation couldn’t have been revealed without political Ideology with its manifesto and the mechanism to spread its messages all over the world. As well, the article reveals that it will not be correct to put Al-Qaeda among the category of the classical terror groups as I have shown in the article as a comparison. Moreover, Al-Qaeda is not similar to any categories of political actor; since the distinction between Jihad and waging war has always been differentiated in the context of Political Islam. Furthermore, my finding reveals the heretic ideology of Al-Qaeda which had spread all over the world and has become an enemy to Islam itself. Harmed the reputation of Islam as a religion. Attention on the ideologic context of Al-Qaeda hasn’t been researched well previously, unknown to majority of the experts. Instead, the attention at most has been put on its ground actions, security concerns and counter terrorism. The article reveals Al-Qaeda’s distinct ideology and its dissimilarity with political actors in the Islamic world, as well as with other liberation movements that is helpful to choose correctly on how to fight against terror in smart methods.